Pemulihan Ekonomi Domestik Terhadap Umkm Terdampak Covid-19 - Saputri, Silvani; Fasa, Muhammad Iqbal (PPJP ULM, 2021)
The COVID-19 pandemic that has hit the world in the last 2 years has an impact on almost the entire global economy, including Indonesia as a result of this pandemic. The domestic economy experienced a significant decline, especially in the national micro, small and medium enterprises sector. The decline in population income affects internal economic inflation. Recovery of population income affects internal economic inflation. This economic recovery is one way to restore the efficiency of the national micro, small and medium enterprises economy. The method used in this research is descriptive qualitative research method. From this research paper, there are results that economic recovery for MSMEs affected by COVID can be carried out well, if there is cooperation between the government and the community as well as national micro, small and medium enterprises, because these contributions are needed so that the domestic economic sector can recover and become good.